Selective Nanoblocker of Cellular Stress Response for Improved Drug‐Free Tumor Therapy. Issue 10 (6th January 2023) - Liu, Cuimei; Cheng, Sihang; Zhou, Xue; Wang, Jue; Mu, Ping; Wang, Zhongyao; Zhang, Lingyu; Li, Lu; Wang, Chungang
Abstract: Nanotechnology‐based drug‐free therapeutic systems using external stimuli can avoid the inherent side effects of drugs and become an attractive therapeutic strategy. However, the cellular stress responses (CSR) are activated encounter with external stimuli, which greatly weaken the efficacy of the drug‐free antitumor. Thus, this work proposes a CSR regulation strategy and synthesizes the glucose oxidase (GOx)‐modified Cu3 BiS3 nanosheets (CBSG NSs) encapsulated by calcium carbonate (CBSG@CaCO3 ) as the novel drug‐free nanoagent. The CBSG@CaCO3 not only cause external stimuli such as energy consumption and oxidative stress damage, but also can destroy the CSR mechanism to guarantee optimal efficacy of starvation‐chemodynamic therapy (ST–CDT). In tumor cells, the CaCO3 shell layer of CBSG@CaCO3 is rapidly degraded, releasing the slowly degradable CBSG NSs with NIR‐II photothermal properties that accelerate the production of external stimuli under laser irradiation. Meanwhile, CaCO3 can block CSR to disrupt the adaptive viability of cancer cells by inhibiting expression of P27 and NRF2. Importantly, the CSR regulation achieves selective treatment on tumor cells based on the difference in physiological conditions between cancer cells and normal cells. This drug‐free cancer therapy with selectivity improves the problem of poor efficacy under the action of CSR, which offers a new avenue in the cancer‐related disease treatment. Abstract : This work proposes a cellular stress response (CSR) modulation strategy and prepares a stepwise degradable CBSG@CaCO3 drug‐free nanoagent as a CSR nanoblocker. Taking advantage of the different physiological characteristics of cancer cells and normal cells, the drug‐free nanoagent selectively disrupts the viability of cancer cells under external stimuli through CSR modulation.